Development of Authentic Psychomotor Instruments for Vocational School in the Covid-19 Pandemic - Latifahtur Rahmah; Sudirman Rizki Ariyanto; Zaldy Iskandar; Irra Chrisyanti Dewi (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2020)
This research aims to develop psychomotoric instruments adapted to the current conditions of Covid-19. Development research was carried out with reference to the 4D model from Thiagarajan. The research sample used was 39 students of the Ottimmo International MasterGourmet Academy. The research instrument used a validation sheet from validators or experts. Data of the research were obtained based on the results of the validation of the experts, which were then analyzed to determine the validity and reliability of the developed psychomotoric instruments. The findings of study indicated that the results of (1) the validation got an average value of 4.61 with a very valid category; and (2) reliability got a value of 0.671 in the reliable category. The conclusion of the research shows that the developed psychomotoric instrument is suitable for use in service and beverage learning.